Intentional endometrial injury enhances angiogenesis through increased production and activation of MMP-9 by TNF-α and MMP-3 in a mouse model. (31st August 2021) - Tu, Yi-An; Chou, Chia-Hung; Yang, Po-Kai; Shun, Chia-Tung; Wen, Wen-Fen; Tsao, Po-Nien; Chen, Shee-Uan; Yang, Jehn-Hsiahn
Abstract: There have been reports of improved pregnancy rates after performing intentional endometrial injuries, also known as endometrial scratching, in patients with recurrent implantation failure. In our previous study on intentional endometrial injury, we found an increased expression of matrix metalloproteinase (MMP)-3 following induced injuries to the mice endometrium. In the current study, we further examine whether the rise in MMP-3 could contribute to increased angiogenesis. Female C57B1/6 mice were obtained at 12 weeks of age, and intentional endometrial injuries were induced mechanically in the left uterine horns. Using the appropriate media, uterine-washes were performed on the injured and uninjured (control) horns of the harvested uteri. The uterine tissues were further processed for tissue lysates, histopathology and immunohistochemistry. The results show that intentional endometrial injuries caused an increase in secreted LPA in the injured horns, which were detected in the uterine-washes. In addition, LPA induced increased production of TNF-α in human endometrial epithelial cells (hEEpCs). Furthermore, TNF-α appeared to induce differential and cell-specific upregulation of the MMPs: MMP-3 was upregulated in the epithelial (hEEpCs), while MMP-9 was upregulated in the endothelial cells (human endometrial endothelial cells; hEEnCs). The upregulation of MMP-3 appeared to be necessary for the activation of MMP-9, whose active form stimulated the formation of vessel-like structure by the hEEnCs. The results of this study suggest that there may be enhanced angiogenesis following intentional endometrial injuries, which is mediated in part by TNF-α-induced and MMP-3-activated MMP-9 production.